Animal Behavior 2016
DOI: 10.1201/b13125-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Transmission of Avoidance Behavior Under Situational Change in Learned and Unlearned Rats

Abstract: Rats emit distinct types of ultrasonic vocalizations, which differ depending on age, the subject's current state and environmental factors. Since it was shown that 50-kHz calls can serve as indices of the animal's positive subjective state, they have received increasing experimental attention, and have successfully been used to study neurobiological mechanisms of positive affect. However, it is likely that such calls do not only reflect a positive affective state, but that they also serve a communicative purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 62 publications
(101 reference statements)
4
35
0
Order By: Relevance
“…one with frequencies around 50 kHz (Burgdorf & Panksepp, 2001;Burgdorf et al, 2008;Burgdorf, Panksepp, & Moskal, 2011;Knutson, Burgdorf, & Panksepp, 2002;Webber et al, 2012;Wöhr & Schwarting, 2007). During rough-and-tumble play, rats emit frequency-modulated 50 kHz USVs (Burgdorf et al, 2008;Himmler, Kisko, Euston, Kolb, & Pellis, 2014;Kisko, Himmler, Himmler, Euston, & Pellis, 2015;Kisko, Wöhr, Pellis, & Pellis, 2016;Knutson et al, 1998), which are emitted in situations normally considered positive or of high reward value, such as receiving or anticipating a food reward or having sex (Burgdorf et al, 2008;Burgdorf et al, 2011;Vanderschuren, 2010).…”
mentioning
confidence: 99%
“…one with frequencies around 50 kHz (Burgdorf & Panksepp, 2001;Burgdorf et al, 2008;Burgdorf, Panksepp, & Moskal, 2011;Knutson, Burgdorf, & Panksepp, 2002;Webber et al, 2012;Wöhr & Schwarting, 2007). During rough-and-tumble play, rats emit frequency-modulated 50 kHz USVs (Burgdorf et al, 2008;Himmler, Kisko, Euston, Kolb, & Pellis, 2014;Kisko, Himmler, Himmler, Euston, & Pellis, 2015;Kisko, Wöhr, Pellis, & Pellis, 2016;Knutson et al, 1998), which are emitted in situations normally considered positive or of high reward value, such as receiving or anticipating a food reward or having sex (Burgdorf et al, 2008;Burgdorf et al, 2011;Vanderschuren, 2010).…”
mentioning
confidence: 99%
“…When analyzing their wheel patterns over days (Fig. 2), we found that low-runners did not increase wheel revolutions (p-values >.05), whereas high-runners showed a running pattern characterized by an increase from day 1 to 5 (p-values <.05), a subsequent plateau (i.e., day [5][6][7][8][9][10][11][12][13][14], and a trend for a decline thereafter. Statistically, high-runners differed from low-runners on days 5-11 and 14 (p-values <.01).…”
Section: Analysis Of Wheel Revolutionsmentioning
confidence: 80%
“…6,11,12,14,15]. Besides their communicative function [13], 50-kHz calls are thought to indicate reward anticipation, incentive motivation [9], and positive affective states [5,6,11,16]) Several rewarding stimuli have been shown to elicit 50-kHz calls conditionally or unconditionally: rough-and-tumbleplay [16,21], tickling [22,23], mating or sexual contact [24], palatable stimuli (e.g., food) [25], electrical brain stimulation [5], and psychostimulatory drugs like amphetamine and cocaine [7,8,26,27]. Also, 50-kHz calls largely depend on dopamine (DA) and norepinephrine function in the brain, especially within the mesolimbic DA system [5-7,27a,27b].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more data have supported the hypothesis that ultrasonic vocalizations in rats serve a communication function [11][12][13][14][15]. Parallel to the communicational role, ultrasonic vocalizations at the 50-kHz band in rats can be an indicator of a positive emotional state which relates to the dopamine level, mu opioid receptor stimulation in the ventral tegmental area, and self-and drug-stimulation of the rewarding systems [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 93%